The Relationship of Non-Diseases with Life Style Drugs - Dimri, Mayank; Rajwar, Virbal Singh; Kush, Luv (Asian Journal of Pharmaceutical Research and Development, 2020)
The concept of non – diseases emerged from clinical slippery. Top 20 non – diseases of non – medical academics were identified. Their relationship with life style drugs was explored.